IMPLEMENTASI KEBIJAKAN PENGEMBANGAN PARIWISATA KAWASAN PANTAI PANJANG KOTA BENGKULU - Delly Delly (Jurnal Manajemen Publik dan Kebijakan Publik (JMPKP), 2019)
ABSTRACT : In welcoming the Wonderfull of Bengkulu 2020 the city of Bengkulu continued to fix the existing tourism area, especially the Long Beach Tourism Village which is a tourist identity in Bengkulu. In the development of the Long Beach Pantai Panjang Tourism area continues to improve but the problems in its development policies, such as cleanliness and inadequate facilities. Through the thesis the problem raised is how is the implementation of tourism development policy in the Long Beach area of Bengkulu city and what are the inhibiting factors.Â  Researchers used descriptive qualitative research methods. The results of this study explain the results of the implementation of tourism development policies in the Pantai Panjang area of Bengkulu city in the Bengkulu City Tourism Office. Cooperation with related agencies is always communicated by the Bengkulu City Tourism Office in the management of Panjang Beach so that Bengkulu in Realizing the Bengkulu 2020 Wonderfull Program